2019
DOI: 10.5539/ijbm.v14n5p123
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on Customers’ Loyalty toward Hotels in Jordan

Abstract: The present study aimed at exploring the impact of social media on customers' loyalty toward the five stars hotels located in Jordan, it also aimed at exploring the impact of satisfaction as a mediating variable on the relationship between social media and customers’ loyalty from the perspectives of customers and marketing managers. In more precise, to measure the mediating effect of satisfaction in the causal relationship between social media and customers’ loyalty toward five star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The concept of satisfaction refers to the conformity between expectations and perceived of service or product (Jun et al, 2004;Martín-Consuegra et al, 2007;Sumaedi et al, 2016), so that the optimizing social media for promotion and providing services to students has reached their expectation, satisfaction, which results in increased attachment. These findings also support previous findings that show social media marketing has a significant effect on satisfaction (Hanaysha, 2017;Zoubi & Al-Harazneh, 2019) and attachment (Ashley & Tuten, 2015;Sashi, 2012).…”
Section: Figure 2 Path Diagramsupporting
confidence: 92%
See 1 more Smart Citation
“…The concept of satisfaction refers to the conformity between expectations and perceived of service or product (Jun et al, 2004;Martín-Consuegra et al, 2007;Sumaedi et al, 2016), so that the optimizing social media for promotion and providing services to students has reached their expectation, satisfaction, which results in increased attachment. These findings also support previous findings that show social media marketing has a significant effect on satisfaction (Hanaysha, 2017;Zoubi & Al-Harazneh, 2019) and attachment (Ashley & Tuten, 2015;Sashi, 2012).…”
Section: Figure 2 Path Diagramsupporting
confidence: 92%
“…Ashley & Tuten (2015) and Sashi (2012) have shown that the use of social media can encourage customer engagement. Apart from having an effect on customer engagement, social media marketing has also been identified as having an effect on satisfaction (Hanaysha, 2017;Zoubi & Al-Harazneh, 2019). This leads to the first (H 1 ) and second (H 2 ) hypothesis.…”
Section: Introductionmentioning
confidence: 95%
“…When we are talking about social media, we refer to: social networks (Facebook, Whatsapp, Twitter, LinkedIn, Instagram), WeChat, Tiktok, Skype, Snapchat, Wblogs, forum, youtube and yahoo answers, etc… Social networking is becoming a more common way to attract consumers and communicate with them (Delafrooz., 2012). Many internet users are active on social media, and a lack of a social media presence for a company will immediately make a negative impact on customers (Faiz et al, 2019: Michael, 2019.…”
Section: Literature Review 21 Social Media Communicationmentioning
confidence: 99%
“…In this regard, numerous companies have used a variety of digital platforms to build preferences and aspirations among consumers in order to increase company efficiency and encourage brand recognition. (Faiz et al, 2019).…”
Section: Literature Review 21 Social Media Communicationmentioning
confidence: 99%
See 1 more Smart Citation